Perancangan dan Pembuatan Hybrid Mobile E-Learning Application di Universitas Kristen Petra - Winsen -; Djoni Haryadi Setiabudi; Lady Joanne Tjahyana (Jurnal Infra, 2013)
Petra Christian University has been using e-learning in the teaching-learning process. However, the e-learning doesn’t exist in the form of mobile application yet. This research is conducted to assist in the teaching-learning process at Petra Christian University by developing a model of mobile e-learning application that can run on cross-platform, which is on Android and BlackBerry platform.The application is created using PhoneGap that uses HTML5, CSS3, and JavaScript. The system on the application follows Lentera e-learning system based on Moodle. On the server side, it takes a modified Moodle’s source code based on PHP so the application can be run in accordance with the system.The result shows that the application can run on cross-platform. The application has a different interface from the website version. The application also runs online with the Lentera system. The basic features of Lentera have been successfully implemented on the application. Assessment of the application as a whole is 55.56% of respondents answered very good, while 44.44% of respondents answered good.